No-reflow phenomenon and triglyceride-glucose index in acute myocardial infarction - Murat Kerkutluoglu; Enes Celik; Musa Dagli; Hakan Gunes (National Scientific Medical Center, 2023)
Objective: The objective of this research was to evaluate the association between the measured triglyceride/glucose index (TyG) and the occurrence of no-reflow phenomena in patients with acute ST-elevation myocardial infarction (STEMI) following primary percutaneous coronary intervention (PCI). Material and methods: This study comprised 242 patients who were treated with primary PCI for acute STEMI. The values of triglycerides and glucose at the time of admission were derived from the patient's file. Using coronary angiography records, the grade of post-procedural thrombolysis in myocardial infarction (TIMI) flow was determined. Results: After PCI, patients were divided into two groups based on their TIMI flow grade: the normal coronary flow group (n=202) and the reduced coronary flow (no-reflow) group (n=40). The group with no-reflow had a poorer left ventricular ejection fraction and a higher prevalence of diabetes compared to the group with normal coronary flow. Individuals with a lower grade of TIMI flow had a substantially higher TyG index (9.7±0.25 vs. 8.8±0.5, p=0.001). The receiver operating characteristic (ROC) curve revealed that the optimal cut-off point of the TyG index for predicting no-reflow was >9.2 with specificity of 72.8% and sensitivity of 97.5% (area under the curve = 0.884; 95% confidence interval, 0.837-0.921; p=0.001). Conclusion: At admission, patients with STEMI who experienced no reflow after primary PCI had a higher TyG index. In such cases, the TyG index can be utilized as a predictor of no-reflow.